How to manage project opportunity and risk : why uncertainty management can be a much better approach than risk management : the updated and re-titled 3rd ed of Project risk management, processes, insights and technoiques - Chapman, C. B.; Ward, Stephen (Stephen C.); Chapman, C. B. (Chichester, West Sussex ; Hoboken, NJ : Wiley, 2012)
Since I wrote the Foreword for the second edition of this book, risk management processes have become much more widely used, but controversy about what should be done and how best to do it has grown. Managing risk is a risky business. Chapman and Ward provide an in-depth explanation of why it is important to understand and manage underlying uncertainty in all its forms, in order to realise opportunities more fully and enhance corporate performance. They show what best practice should look like. The implications go well beyond the conventional wisdom of project risk management, providing an enl.
Uncertainty in and around projects -- Uncertainty, risk and opportunity -- Key motives for uncertainty management -- An overview of generic process frameworks -- Define the project -- Focus the process -- Identify all the relevant sources of uncertainty, response options and conditions -- Structure all uncertainty -- Clarify ownership -- Quantify some uncertainty -- Evaluate all the relevant implications -- Fully integrating the strategy shaping stages -- Fully integrating the strategy implementation stages -- Developing PUMP capability as a project -- Contracts and governance as frameworks for enlightened relationship management -- A corporate capability perspective.
Revised edition of: Project risk management, c2003.
Includes bibliographical references and index.
English.
John Wiley and Sons
Keywords: Project management; Risk management; Gestion de projet; Gestion du risque; risk management; BUSINESS & ECONOMICS -- Project Management; TECHNOLOGY & ENGINEERING -- Project Management; Project management; Risk management